Pendampingan Peran Digital Marketing dan Pemasaran dalam Upaya Keberlangsungan Hidup pada UMKM yang tergabung dalam SiBakul - Zulia Putri, Anandita; Nusron, Lulu Amalia; Fachrunnisa, Zidni Husnia; Pramudiati, Ningrum; Adyaksana, Rahandhika Ivan (LPPM IST AKPRIND Yogyakarta, 2022)
MSMEs in Yogyakarta is growing rapidly because Yogyakarta is one of the city's tourist destinations and is known as a student city and a city of culture. One of the obstacles for MSMEs is related to financing to obtain expansion and marketing capital that has not been maximized. SiBakul is an MSME collection data system so that registered MSME development can be more focused. The Service Team provides guidance and direction related to the digital marketing system and MSME financing. This marketing system aims to expand the MSME market and fostering the submission of a financing system aims to encourage MSMEs to be able to expand. This coaching activity is carried out for 1 month, which consists of activities for developing a digital marketing system, financing education, directing MSMEs to apply for financing, and the last stage is the evaluation stage.